2023
DOI: 10.1002/adma.202208590
|View full text |Cite
|
Sign up to set email alerts
|

Weakening Li+De‐solvation Barrier for Cryogenic Li–S Pouch Cells

Abstract: Li–S batteries hold promise for pushing cell‐level energy densities beyond 300 Wh kg‐1 while operating at low temperatures (LTs, below 0 °C). However, the capacity release of existing Li–S batteries at LTs is still barely satisfactory, and there is almost no verification of the practicability of Li–S batteries at LTs in the Ah‐level pouch cell. Here, antecedent molecular dynamics (MDs) combined with density functional theory analysis are used to systematically investigate Li+ solvation structure in conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Many literatures have proposed that the de-solvation barriers of solvated ions at the interface of the electrode/electrolyte under low temperature is the main obstacle for achieving good low-temperature performance. [49][50][51] Therefore, it can be deduced that excellent electrochemical performance of COP/Cu@Zn anode at low temperature is due to desolvation of Zn ion under the help of COP layer. In a word, effect of COP layer in realizing de-solvation of Zn ion and regulating Zn deposit ensures high reversibility of COP/Cu@Zn anode.…”
Section: Resultsmentioning
confidence: 99%
“…Many literatures have proposed that the de-solvation barriers of solvated ions at the interface of the electrode/electrolyte under low temperature is the main obstacle for achieving good low-temperature performance. [49][50][51] Therefore, it can be deduced that excellent electrochemical performance of COP/Cu@Zn anode at low temperature is due to desolvation of Zn ion under the help of COP layer. In a word, effect of COP layer in realizing de-solvation of Zn ion and regulating Zn deposit ensures high reversibility of COP/Cu@Zn anode.…”
Section: Resultsmentioning
confidence: 99%
“…Specically, solvent molecules explicitly bond with solutes, and the (de)solvation energy would be distinct when solutes are coordinated by different numbers of solvents, namely in different solvation statuses (e.g., non-solvated, partially solvated, and fully solvated). [35][36][37] Lin et al found that varying the concentration of electrolytes results in different solvation statuses of poly-suldes, thus signicantly affecting the open circuit voltage of batteries. 38 Whether the solvation statuses of sulfur species affect the generation of trisulfur radicals is worthy of in-depth exploration.…”
Section: mentioning
confidence: 99%
“…, non-solvated, partially solvated, and fully solvated). 35–37 Lin et al found that varying the concentration of electrolytes results in different solvation statuses of polysulfides, thus significantly affecting the open circuit voltage of batteries. 38 Whether the solvation statuses of sulfur species affect the generation of trisulfur radicals is worthy of in-depth exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the advantages of sulfur, which has low cost, is easily available, and environmentally friendly, have also attracted wide attentions. [5][6][7][8] However, The 'shuttle effect' and lithium anode corrosion have always restricted the development of Li-S batteries. During the charging and discharging process, the soluble lithium polysulfides (Li 2 S x , 2 < x ≤ 8) are formed and dissolved in the electrolyte, resulting in the loss of active sulfur and corrosion of lithium anodes, which leads to the sharp capacity decline and poor safety performance.…”
Section: Introductionmentioning
confidence: 99%